Partial sequential testing for comparing two univariate normal distributions - Basak, Sancharee; Bandyopadhyay, Uttam; Biswas, Atanu (Sequential analysis, 2025)
This article provides a two-stage procedure to develop a partial sequential test procedure for both the location and scale parameters of a normal distribution. The first stage is taken to be of a fixed sample size. The stopping rule is obtained by adopting a two-stage procedure on the number of index subjects using an inverse sampling scheme in the second stage. Different asymptotic results associated with the procedure are obtained. The findings are supported by detailed simulation studies followed by three data illustrations.